PTH-025 Which patients tolerate unsedated colonoscopy? a uk bowel cancer screening centre experience. (22nd June 2015) - Ansari, S; Smith, L-A; Mayers, R; Yu, C
Abstract : Introduction: In the UK Bowel Cancer Screening Programme (BCSP), sedation doses and comfort scoring are used in quality assurance. There is debate whether we should offer unsedated colonoscopy, nitrous oxide being available in many units. This is a double edged sword; endoscopists are using less sedation and analgesia but potentially increase discomfort for patients. There is marked diversity in the Bradford and Airedale area with an approximate 20% South Asian population. We wanted to know if we could predict patients who would choose to have their colonoscopy unsedated. Previous studies within the Bradford and Airedale BCSP have shown differences in uptake related to ethnicity and deprivation indices. Our question was whether these also play a role in the tolerance of colonoscopy. Method: Retrospective analyses of all BCSP cases performed by a single endoscopist at Bradford Royal Infirmary (BRI) were reviewed between February 2010 and April 2014. This endoscopist routinely offered a choice of sedation to all patients: 1. No medication but Fentanyl and then Midazolam if required 2. Fentanyl at the start then Midazolam if required 3. Combination of Fentanyl and Midazolam Data collected was gender, ethnicity, postcode and deprivation index, Fentanyl and Midazolam doses used. Results: In total, 453 colonoscopies were performed. Midazolam was not used in 219 cases (48%). Neither drug was used in 20% of cases (80 Males, 9 Females). Only 5 Asian males and no Asian females had a drug-free procedure. In 130 cases (29%), Fentanyl was the only medication used. Just 7% of Asian females had Fentanyl only compared to 27% of Caucasian females. Use of both drugs was highest in Asian females (93%) compared to Caucasian females (67%). Analysis of deprivation index of patients using their postcode showed no difference in sedation uptake. Conclusion: There was a clear difference in the use of sedation within the group. Several factors may influence patient choice regarding sedation. The first being language barriers; being offered unsedated colonoscopy may be erroneously interpreted as having no option of medication if it becomes uncomfortable. Choosing sedation may be driven by other cultural elements. Colonoscopy is an invasive procedure and may be seen as embarrassing or shameful, these fears are known barriers to screening uptake. Fear of pain and being diagnosed with cancer may also influence choice. However, some are quick to avoid medication when given a choice. Having no sedation or Fentanyl reduces the need for someone to collect or stay with the patient. This was seen more with those who lived on their own, not having to stay with family or friend post procedure. When offering all patients unsedated colonoscopy we should be mindful that not all will tolerate or want it. Disclosure of interest: None Declared.